Gastrointestinal bleeding risk with rivaroxaban vs aspirin in atrial fibrillation: A multinational study - Laura Fanning (2020)
© 2020 The Authors. Pharmacoepidemiology and Drug Safety published by John Wiley & Sons Ltd. Purpose: Comparative gastrointestinal bleeding (GIB) risk between rivaroxaban and low-dose aspirin is unknown in patients with atrial fibrillation (AF). This study investigated GIB risk with rivaroxaban vs aspirin among two separate AF cohorts in Hong Kong and the United Kingdom, using a common protocol approach. Methods: This was a population-based cohort study using separate data from the Clinical Data Analysis and Reporting System (CDARS) of the Hong Kong Hospital Authority (2010-2018) and The Health Improvement Network (THIN) database in the United Kingdom (2011-2017). Patients with AF newly prescribed aspirin or rivaroxaban were included. Cox proportional hazards regression was used to compare GIB risks for rivaroxaban vs aspirin, accounting for confounders using propensity score fine stratification approach. Results: In CDARS, 29 213 patients were included; n = 1052 (rivaroxaban), n = 28 161 (aspirin). Crude GIB event rates per 100 patient-years in CDARS were 3.0 (aspirin) and 2.6 (rivaroxaban). No difference in GIB risk was observed between rivaroxaban and aspirin overall (HR = 1.04, 95%CI = 0.76-1.42), and in dose-stratified analyses (HR = 1.21, 95%CI = 0.84-1.74 [20 mg/day]; HR = 0.80, 95%CI = 0.44-1.45 [≤15 mg/day]). In THIN, 11 549 patients were included, n = 3496 (rivaroxaban) and n = 8053 (aspirin). Crude GIB event rates were 1.3 (aspirin) and 2.4 (rivaroxaban) per 100 patient-years. No difference in GIB risk was observed between rivaroxaban and aspirin overall (HR = 1.40, 95%CI = 1.00-1.98) and low-dose rivaroxaban (≤15 mg/day) (HR = 1.00, 95%CI = 0.56-1.30), but increased GIB risk was observed for rivaroxaban 20 mg/day vs aspirin (HR = 1.57, 95%CI = 1.08-2.29). Conclusion: In patients with AF, GIB risk was comparable between aspirin and rivaroxaban ≤15 mg/day. GIB risk for rivaroxaban 20 mg/day vs aspirin remains uncertain and warrants further investigation.